2018
DOI: 10.3390/ijerph15071436
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Heat Waves on Emergency Department Admissions in Charlottesville, Virginia, U.S.A

Abstract: Heat waves have been linked to increases in emergency-related morbidity, but more research is needed on the demographic and disease-specific aspects of these morbidities. Using a case-crossover approach, over 700,000 daily emergency department hospital admissions in Charlottesville, Virginia, U.S.A. from 2005–2016 are compared between warm season heat wave and non-heat wave periods. Heat waves are defined based on the exceedance, for at least three consecutive days, of two apparent temperature thresholds (35 °… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 112 publications
4
14
0
Order By: Relevance
“… 32 91 92 During heatwaves, pregnant women might also have higher rates of admission to hospital emergency departments and increased cardiovascular events, such as stroke and myocardial infarction. 93 94 Some studies have also linked emotional stress and sleep disturbance in pregnancy to hot weather. 95 96 Group B streptococcus colonisation of the vagina and cervix of pregnant women could increase at higher ambient temperatures, 97 raising risks for newborn sepsis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 32 91 92 During heatwaves, pregnant women might also have higher rates of admission to hospital emergency departments and increased cardiovascular events, such as stroke and myocardial infarction. 93 94 Some studies have also linked emotional stress and sleep disturbance in pregnancy to hot weather. 95 96 Group B streptococcus colonisation of the vagina and cervix of pregnant women could increase at higher ambient temperatures, 97 raising risks for newborn sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…Heat exposure is implicated in many conditions in pregnant women, with evidence pointing to heat effects on pre-eclampsia, prolonged labour, and antepartum or postpartum haemorrhage 329192. During heatwaves, pregnant women might also have higher rates of admission to hospital emergency departments and increased cardiovascular events, such as stroke and myocardial infarction 9394. Some studies have also linked emotional stress and sleep disturbance in pregnancy to hot weather 9596.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of climate change on the emergency care system are well described in HICs (Aitken et al, 2015;Bucher et al, 2018;Chowdhury et al, 2019;Davis & Novicoff, 2018;Doran et al, 2016;Ghazali et al, 2018;Hess, Saha, & Luber, 2014;Hutchinson et al, 2018;Lee et al, 2016;Liang & Messenger, 2018;Malik et al, 2018;McQuade et al, 2018). This data suggests that climate change is likely to increase the incidence of emergency conditions, disproportionately affect patients who rely on acute care in emergency units, present marked increases in vector-borne and environmentally driven diseases, and stress current emergency systems with increased frequency and severity of disasters.…”
Section: Emergency Care Systems and Climate-related Health Effectsmentioning
confidence: 99%
“…While the effects of temperatures on mortality have been well documented, less is known about their impact on morbidity. Different outcomes have been examined, such as hospital admissions [48], emergency department visits [913], outpatient visits [14] or general practice (GP) visits [15], with inconsistent results. For example, an overview of systematic reviews including twenty articles reported no significant heat effects for cardiovascular and cerebrovascular morbidity after conducting a meta-analyses, while a positive association with heat was found for respiratory morbidity among the elderly [16].…”
Section: Introductionmentioning
confidence: 99%